2023
DOI: 10.1021/acs.joc.3c01234
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Synthesis of Phenanthridines via Pd(II)-Catalyzed Annulative C(sp2)–H Activation

Anamika Yadav,
Surabhi Upadhyay,
Ruchir Kant
et al.

Abstract: A robust synthesis of phenanthridines has been described via Pd(II)-catalyzed domino C(sp2)–H activation/N-arylation using oxime esters with aryl acyl peroxides in a highly regioselective manner. This protocol is compatible with acetophenone as well as benzophenone-derived oxime esters and allows modular construction of functionalized phenanthridines with wide tolerance of electronic functionality. Further transformations were conducted to synthesize key building blocks, and control experiments were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Further investigation revealed that the types of supporting electrolytes also significantly affected the reaction efficiency ( [20][21][22][23][24][25]. Decreasing of the current density from 17.3 mA cm À 2 to 13.5 and 9.6 mA cm À 2 or increasing it to 23.1, 30.8, 38.5 and 57.7 mA cm À 2 afforded 2 a in modest to low yields (Table 1, entries [26][27][28][29][30][31]. Slightly lower yield was observed when the reaction temperature was raised to 80 °C (Table 1, entry 32).…”
Section: Resultsmentioning
confidence: 99%
“…Further investigation revealed that the types of supporting electrolytes also significantly affected the reaction efficiency ( [20][21][22][23][24][25]. Decreasing of the current density from 17.3 mA cm À 2 to 13.5 and 9.6 mA cm À 2 or increasing it to 23.1, 30.8, 38.5 and 57.7 mA cm À 2 afforded 2 a in modest to low yields (Table 1, entries [26][27][28][29][30][31]. Slightly lower yield was observed when the reaction temperature was raised to 80 °C (Table 1, entry 32).…”
Section: Resultsmentioning
confidence: 99%